The challenges of implementing Islamic finance products and services practice in Malaysia. - Mohammad Aimi Mohd Zubir; Nur Qistina Suhaimi; Nur Salsabila Mohd Israj; Nur Syafika Jailani (2022)
The main objectives of this study is to identify the relationship between awareness, unclear information, security, privacy and lack of standard issues and the challenge influencing of implementing Islamic Finance Products and Services. The research design is used quantitative methods and data collection was done by using an online questionnaire. This study uses Pearson Correlation and Multiple Linear Regression to analyse the data, and the data was gathered by distributing the online questionnaire of the sample of 384 which taken from the total populations of the Islamic Finance users in Malaysia. The findings shows the correlations between awareness, unclear information, security, privacy & lack of standard and the challenges of implementing Islamic finance products and services practice in Malaysia are significant. Based on Multiple Linear Regression analysis, all the challenges are closely influencing the challenges. The comprehensive adoption of Islamic finance Products and services in Malaysia will give a new impetus to the Islamic Finance institutions as one of the important needs of consumers of the Islamic Finance Products and services in Malaysia.